SORCERER’S APPRENTICE (JERZY FICOWSKI AND JULIAN TUWIM MEET ON A GYPSY TRAIL) - Kandziora, Jerzy (Porównania, 2014)
Based on archival correspondence between the two poets, the sketch reconstructs the early period of Jerzy Ficowski’s interest in the Romani people, together with his acquaintance with Julian Tuwim and the latter’s benevolent albeit ambivalent – highly ideologised - patronage. In the period’s Stalinist political context, the mutual intellectual attraction of the two personalities had also negative consequences. The precarious situation that involved Ficowski-the researcher crossing the borders of insular Romani customs and, simultaneously, introducing the Romani poet Bronisława Wajs (Romani name: Papusza) into the official literary mainstream tainted by ideology, was, therefore, particularly dramatic. Ostracism of the Romani community, which eventually banished Papusza, proved to be the price for presenting her poetry to a wider range of readers. The ensuing sense of threat she experienced eventually led to a mental disorder.